LAPAROSCOPIC RESECTION OF GASTROINTESTINAL STROMAL TUMOR OF THE STOMACH - CASE REPORT AND CONCISE LITERATURE REVIEW - Svetlana Shumarova; Anton Koichev; Tsvetelina Mihaylova (Peytchinski Publishing, 2024)
Purpose: To describe the effectiveness of laparoscopic partial gastric resection for small GIST of the stomach Case presentation: We present a 69-year-old woman with gastric GIST, diagnosed by ultrasound measuring about 3 cm/d on CT. Laparoscopic gastric resection was performed using Endo-GIA. GIST was proven immunophenotypically based on co-expression of CD 117+low (membrane and cytoplasmic expression) and membranous expression of CD34 with lines free from tumor infiltration. Conclusion: Laparoscopic resection is a safe procedure, oncologically and technically feasible, when in the hands of an experienced surgeon.